DNA Profiling in Forensic Dentistry - M. Laksita1 , K. R. Don2 , Jothi Priya A3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The recent advances in molecular biology have revolutionized all aspects of dentistry. Deoxyribose NucleicAcid (DNA), the language of life yields information beyond our imagination with respect to our bodyhealth conditions. DNA is present in chromosomes and is responsible for storing all the genetic materialand they are not the same for all individuals. Forensic dental comparison has been used for identification ofhumans in cases where body tissues are damaged or prolonged exposure to the environment has made theidentification impractical. The use of DNA profile tests in forensic dentistry provides a new perspective inhuman identification. This article summarizes the recent literature on use of this technique in identificationof unidentified human remains, highlighting the importance of DNA in the cases of forensic investigation.